Climatic trend and the retreat and disintegration of ice shelves on the Antarctic Peninsula: an overview - Skvarca, Pedro; Rack, Wolfgang; Rott, Helmut; Ibarzábal Donángelo, Teresa (Polar Research, 1999)
Observation of the retreat and disintegration of ice shelves around the Antarctic Peninsula during the last three decades and associated changes in air temperature, measured at various meteorological stations on the Antarctic Peninsula, are reviewed. The climatically induced retreat of the northern Larsen Ice Shelf on the east coast and of the Wordie, George VI, and Wilkins ice shelves on the west coast amounted to about 10 000 km2 since the mid-1960s. A summary is presented on the recession history of the Larsen Ice Shelf and on the collapse of those sections north of Robertson Island in early 1995. The area changes were derived from images of various satellites, dating back to a late 1963 image from the recently declassified US Argon space missions. This photograph reveals a previously unknown, minor advance of the northern Larsen Ice Shelf before 1975. During the period of retreat a consistent and pronounced warming trend was observed at the stations on both east and west coasts of the Antarctic Peninsula, but a major cause of the fast retreat and final collapse of the northernmost sections of the Larsen Ice Shelf were several unusually warm summers. Temperature records from the nearby station Marambio show that a positive mean summer temperature was reached for the first time in 1992-93. Recent observations indicate that the process of ice shelf disintegration is proceeding further south on both sides of the Antarctic Peninsula.
Keywords: Antarktis; brehylle; glasiologi; isbrem; isshelf; klimaendringer; meteorologi; satellittbilder

Oxygen 18 and helium as tracers of ice shelf water and water/ice interaction in the Weddell Sea - Schlosser, Peter; Bayer, Reinhold; Foldvik, Arne; Gammelsrød, Tor; Rohardt, Gerd; Münnich, Karl Otto (Journal of Geophysical Research: Oceans, 1990)
Oxygen 18 and helium isotope data from stations located in the Filchner Depression, on the continental slope of the southern Weddell Sea, and in the central Weddell Sea are presented and discussed. The 18O and 4He signals imprinted on the water circulating under the Filchner/Ronne Ice Shelf (Ice Shelf Water, or ISW) due to melting of glacial ice at the base of the ice shelf are traced across the sill separating the Filchner Depression from the Weddell Sea. Low δ18O values are correlated with high 4He concentrations in the ISW found in the Filchner Depression (minimum δ18O values: −0.8‰; maximum 4He concentrations: about 4.7×10−8 cm3 STP g−1). The fraction of glacial meltwater contained in the ISW found in the Filchner Depression is estimated to about 6 to 7‰. The 18O and helium isotope data from the overflowing shelf water component observed on the continental slope confirm the hypothesis that ISW contributes significantly to the Weddell Sea Bottom Water (WSBW). On the basis of a inultiparameter water mass analysis it is discussed which fraction of the WSBW originates from ISW and which other shelf waters potentially could contribute to WSBW.
Keywords: Sørishavet; Weddellhavet; brehylle; geofysikk; hydrografi; isbrem; isshelf; oseanografi; smeltevann; vannmasser

The response of Antarctic icebergs to ocean waves - Wadhams, Peter; Kristensen, Monica; Orheim, Olav (Journal of Geophysical Research: Oceans, 1983)
The heave, tilt, and strain responses of three Antarctic tabular icebergs to ocean waves were measured during a 1980–1981 cruise of HMS Endurance to the South Atlantic. The three icebergs, located near the South Sandwich and South Orkney islands, were instrumented with accelerometers, tiltmeters, and wire strainmeters, while a Waverider buoy was used to record the ocean wave field. The thickness of the icebergs was surveyed by a helicopter-borne radio echo sounder. The heave response occurred mainly at the swell period but with outbreaks of bobbing which lasted for a few cycles at a resonant period (about 40 s), which agreed well with the predictions of a numerical finite element model. The roll response occurred mainly at a long resonant period (40–50 s), which again agreed well with the model, but there was also a significant response at ocean wave periods (5–20 s), which exceeded predictions. The strain response had a component at very long periods, which is unexplained by theory, while the surface strain at ocean wave periods agreed with the simple analytical model of Goodman et al. (1980). Using this model it is possible to predict a wave height and period that will cause breakup of the icebergs, and we conclude that swell-induced breakup is likely to occur during major storms in the open southern ocean.
Keywords: Sør-Orknøyene; Sørishavet; brehylle; geofysikk; glasiologi; havbølger; isberg; isbreer; isbrem; isfjell; isshelf; oseanografi